Immigration and anti-immigrant sentiments: Evidence from the 2017 German parliamentary election - Kim Leonie Kellermann; Simon Winter (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2018)
We empirically examine the relationship between shares of foreigners in a district and the share of votes cast in that district for the Alternative für Deutschland (AfD), the major anti-immigrant party in the 2017 German parliamentary election. The classic theory on the political economy of migration supposes that immigration fosters opposing sentiments among the natives due to fiercer competition for jobs, housing and public goods. Notably, the vote distribution in the 2017 election suggests that AfD vote shares are higher in districts with fewer foreign inhabitants. We exploit administrative data on election results and district-specific features to study a potentially causal effect. As the share of foreigners in a district may be endogenous, we apply an IV approach, using the number of working permits as an instrument for the share of foreign residents. Our results corroborate the Contact Theory, which states that more intensive exposure to and contact with immigrants reduce the propensity for anti-immigrant voting. We find that a 10 % increase in the population share of foreigners is associated with a 2.6 % lower vote share for the AfD. By contrast, a strong increase in the number of asylum seekers positively adds to AfD support.
Keywords: D72; D91; J15; 330; migration; anti-immigrant parties; contact theory; ethnic competition; economic competition